Following the genes: a framework for animal modeling of psychiatric disorders. - MITCHELL, KEVIN (My University, 2011)
The number of individual cases of psychiatric disorders that can be ascribed to identified, rare, single mutations is increasing with great rapidity. Such mutations can be recapitulated in mice to generate animal models with direct etiological validity. Defining the underlying pathogenic mechanisms will require an experimental and theoretical framework to make the links from mutation to altered behavior in an animal or psychopathology in a human. Here, we discuss key elements of such a framework, including cell type-based phenotyping, developmental trajectories, linking circuit properties at micro and macro scales and definition of neurobiological phenotypes that are directly translatable to humans.
PUBLISHED
Keywords: Neuroscience; Genetics; theoretical framework; Genes & Society; Neuroscience